Oil palm by product as an alternative feedstuff in Central Kalimantan: 1. The effect of feeding palm oil mill effluent on broiler’s performance - Ermin Widjaja; Wiranda G Piliang; Iman Rahayu; Bambang Ngaji Utomo (Jurnal Ilmu Ternak dan Veteriner, 2006)
Palm oil mill effluent, a by product of crude palm oil processing, is found in an exessive amount in Central Kalimantan. It is estimated that 400 ton of this material is produced per day by crude palm oil (CPO) factory in this region. This material contains 12.63-17.41% crude protein, 9.98-25.79% crude fiber, 7.12-15.15% crude fat and 3217-3454 kcal/kg (gross energy). An experiment was conducted on broiler chickens of Hubbard strain in Kapuas District. The objectives of the experiment was to study the performance of broilers fed solid in the diet. The experiment was arranged in a completely randomized design. The treatments were levels of solid in the diet, i.e., 0.0, 12.5, 25.0 and 37.5%. Four hundred broilers were devided into 4 treatment groups with 5 replications, consisted of 20 chickens in each replicate. The results of this experiment showed that diet containing 0.0, 12.5, 25.0 and 37.5% of solid respectively produced final live weight of broilers 2508, 2229 and 1880 g respectively, whereas control (0.0% of solid) was 2712 g. Feed conversion of the treatments were 2.39, 2.76, 3.24 respectively and without solid as control was 2.36. It is concluded that diet containing as much as 12.5% of solid can be used in broiler ration. Key Words: Solid, Broiler Chickens, Performance